Green firebreaks as a management tool for wildfires: Lessons from China. (1st March 2019) - Cui, Xinglei; Alam, Md Azharul; Perry, George LW.; Paterson, Adrian M.; Wyse, Sarah V.; Curran, Timothy J.
Abstract: Wildfire is a widespread natural hazard that is expected to increase in areal extent, severity and frequency with ongoing changes in climate and land-use. One tool that has been used in an effort to reduce the damage caused by wildfires is green firebreaks: strips of low-flammability vegetation grown at strategic locations in the landscape. Green firebreaks are increasingly being recommended for wildfire management and have been implemented in many countries. The approach is particularly widely used in China, where more than 364, 000 km of green firebreaks have been planted and a further 167, 000 km are planned for construction before 2025. China is not only a world leader in the implementation of green firebreaks but has also led the way in testing the effectiveness of green firebreaks and in providing guidelines for green firebreak construction. However, most of this research has been reported in the non-English literature, and so is inaccessible to many readers. Here we review the extensive research on the construction and effectiveness of green firebreaks in China and examine how the lessons learned from this research could contribute to the effective implementation of green firebreaks globally. Chinese studies suggest that the ideal species for green firebreaks should meet trait requirements from three perspectives: ecological, silvicultural and economic. Green firebreaks with a multi-layered structure and a closed canopy have the potential to be an effective, long-term, biodiversity-friendly and low-cost tool for fire suppression, although they complement rather than replace other more traditional fire suppression approaches. Graphical abstract: Image 1 Highlights: China has planted 364, 000 km of green firebreaks to suppress fire. Chinese scientists provide useful guidelines on green firebreak creation, structure and layout. Field-based experiments show that green firebreaks can stop high intensity fires. Green firebreaks can be effective, biodiversity-friendly, low-cost tools for fire suppression.